High energy oral supplements may suppress appetite without benefiting growth. (24th May 2012) - Chillingworth, A; Wright, CM
Abstract : Introduction and aims: High energy oral supplements ('sip feeds') are widely prescribed but poorly evaluated in the paediatric population. In our feeding clinic many children referred with feeding behaviour problems are long term sip feed users and we have noticed striking improvements in eating behaviour and sometimes weight gain when these were stopped. As a result, the clinic now has a policy of stopping sip feeds unless they are obviously essential. This study set out to formally audit the effect of stopping sip feeds on weight and feeding behaviour. Method and subjects: A retrospective review of notes for all 38 children referred to a tertiary feeding clinic on long term sip feeds between 2002-10, where feed reduction was deemed appropriate. Results: At first appointment the children were median age 3.5 years (range 0.7-10 years) and 47% (18) had neurodevelopmental problems. Only 26% (10) children were referred specifically for withdrawal of sip feeds and 40% (15) for general help with feeding behaviour, while 32% (12) were referred because of poor weight gain. Supplement reduction was commenced immediately for 67% (24). Improvement in feeding behaviour after feed reduction was documented for 94% (36) children. When follow up closed, 80% (30) had stopped sip feeds altogether. Three children remained on lower volumes of sip feeds, one had died due to unrelated reasons and 4 were lost to follow up. Of the 29 who had weight data at last follow up, only 10% (3) ever fell more than one centile space after feed withdrawal (min −0.88 SD), 21 were within ±1 centile space, and 5 (17%) were 1-2 spaces higher (max +1.6 SD). Conclusion: A majority of children on sip feeds showed improved eating behaviour after feed reduction, no worsening of weight gain and 1 in 6 showed improved weight gain. This suggests that use of sip feeds produces food refusal and in some children may suppress appetite sufficiently to cause reduced total intake.